2016
DOI: 10.1186/s12904-016-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes we can’t fix things”: a qualitative study of health care professionals’ perceptions of end of life care for patients with heart failure

Abstract: BackgroundAlthough heart failure has a worse prognosis than some cancers, patients often have restricted access to well-developed end of life (EoL) models of care. Studies show that patients with advanced heart failure may have a poor understanding of their condition and its outcome and, therefore, miss opportunities to discuss their wishes for EoL care and preferred place of death. We aimed to explore the perceptions and experiences of health care professionals (HCPs) working with patients with heart failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 45 publications
1
51
0
1
Order By: Relevance
“…A preoccupation reflected by participants in the study was the lack of communication between caregivers and patients, which mainly involves doctors who do not clearly communicate information on the stage of the disease. Such results corroborate the observations of Glogowska (16) regarding the conversation on advanced illness of patients. In palliative care, communication is an efficient therapeutic resource (17)(18)(19).…”
Section: Perceptions By Families On Organizational Problems In the Casupporting
confidence: 91%
“…A preoccupation reflected by participants in the study was the lack of communication between caregivers and patients, which mainly involves doctors who do not clearly communicate information on the stage of the disease. Such results corroborate the observations of Glogowska (16) regarding the conversation on advanced illness of patients. In palliative care, communication is an efficient therapeutic resource (17)(18)(19).…”
Section: Perceptions By Families On Organizational Problems In the Casupporting
confidence: 91%
“…5,6 In this context, prognostication can present practical challenges, 7,8 and the symptom burden associated with HF makes it a complex condition for healthcare professionals to clinically manage. Often, clinicians, patients, and caregivers are unaware of the poor prognosis, 9,10 mitigating the potential for end-of-life conversations, such as patients" preferred place of death. 7 Evidence indicates that, given a choice, most people would prefer to be cared for and die at home.…”
mentioning
confidence: 99%
“…Five UK qualitative papers were identified. Four of these papers reported findings from the HoldFAST study, [126][127][128][129] and some of those identified were not from the mapping review but from supplementary follow-up of citations and references. The HoldFAST study was a multicentre study co-ordinated across the University of Bristol, the University of Oxford and Keele University and funded by NIHR.…”
Section: Number and Type Of Uk Studies Identifiedmentioning
confidence: 99%
“…132 Both primary and secondary care physicians in the HoldFAST study acknowledged that they were unsure about what services were available or that there were few services on which they could call. 129 People with chronic conditions may also use health services inappropriately, delaying their presentation to a GP or hospital (PT4) because of perceptions of the service either anticipated or based on the past experience of either themselves or others. Some patients may also feel a reluctance to seek medical advice if they perceive that their previous actions may have contributed to their condition (as in the case of smoking and COPD 131 ).…”
Section: Operating Programme Theoriesmentioning
confidence: 99%
See 1 more Smart Citation